(untitled) (Research, Society and Development, 2019)
Civil construction is a sector that contributes with huge amounts of waste deposited in the environment and removes much of its raw material from nature, and the processing of some of these raw materials is highly polluting. The search for minimizing the environmental impacts of this activity motivates the study of materials that may integrate the concrete in order to supply the sector demands. The present study aims to analyze the use of rice husk ash as a replacement for cement, and of recycled aggregate, in partial replacement of aggregate. Two types of concrete were evaluated through physical and mechanical tests, the first using only cement and natural aggregates, and the second using 10% rice husk ash and 25% mixed recycled aggregate. The results indicate that there are significant differences between the natural and recycled aggregates, especially absorption and porosity. These differences reflected in lower resistance and lower modulus of elasticity, however, it is possible to confirm the feasibility to use the recycled aggregates in the manufacture of structural concrete.